Industry 4.0 and Education 4.0 : Expected Competences and Skills in Society 5.0 - Tumentsetseg, Enkhjav; Varga, Erika (Acta Carolus Robertus, 2022)
We are currently in the midst of the fourth industrial revolution, which will bring about more profound changes than any previous industrial revolution. This article examines the concept of Industry 4.0, Education 4.0 as well as certain HR challenges associated with this new era of digitalization, automation, and computerization. The major goal of this research is to emphasize the need of paying attention to the growth and direction of this smart technology trend, as well as the competencies and abilities that will be required in future workplaces. Technical as well as soft skills are listed and some practical usage of the smart technologies in the educational sector is highlighted. The critical role of the universities in accelerating the transition to a highly digitalized and automated society, like Society 5.0 is emphasized. Based on the previously available literature and some reports, the conclusion and recommendation part is drawn.
Keywords: Industry 4.0; Education 4.0; Society 5.0; automation and digitalization; competence and skills